Association between fruit intake and abdominal adiposity in 1,707 randomly selected U.S. children - Tucker, Larry A. (Frontiers in Nutrition, 2025)
BackgroundThis investigation was conducted to determine the relationship between fruit intake and abdominal adiposity in 1,707 U.S. children.MethodsThe children were randomly selected as part of the National Health and Nutrition Examination Survey (NHANES), so the sample represented U.S. children 8–11 years old. A cross-sectional design was employed. Fruit consumption was measured using the average of two 24-h dietary recalls. Fruit intake was expressed as the percent of total energy derived from fruit, not including fruit juices. Abdominal adiposity was indexed using two methods: waist circumference and the sagittal abdominal diameter (SAD). Covariates were age, sex, race, household size, year of assessment, recreational computer time, physical activity, total energy consumption, and intake of carbohydrate, protein, fat, fiber, sugar, and saturated fat. The outcome measures were waist circumference and sagittal abdominal diameter.ResultsAccording to the findings, mean fruit consumption was 10.1% of total energy intake. With fruit intake and abdominal adiposity both treated as continuous variables, after controlling for all the covariates, there were significant inverse linear relationships between the log10 of fruit intake and waist circumference (F = 6.5, p = 0.0143) and SAD (F = 7.0, p = 0.0112). Similarly, with fruit consumption divided into 3 categories (None, Low, and Moderate/High), means of the abdominal adiposity variables differed across the fruit categories in a dose–response pattern (SAD: F = 3.4, p = 0.0407; Waist: F = 2.9, p = 0.0657), after adjusting for all the covariates.ConclusionIn this nationally representative sample of U.S. children, fruit consumption was low. Higher levels of fruit consumption were predictive of lower levels of abdominal adiposity. These findings support the recommendation of the U.S. Dietary Guidelines for Americans that encourage children to eat more fruit. Given the results, physicians, teachers, and parents should educate and encourage children about the importance of fruit consumption.